2005
DOI: 10.1016/j.jhsb.2005.06.017
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study of the Anterior Interosseous Nerve and its Innervation of the Pronator Quadratus Muscle

Abstract: This anatomical study of 40 upper limbs from cadavers investigated the branching pattern of the anterior interosseous nerve in its distal part using the operating microscope. An articular branch to the wrist joint and/or the distal radioulnar joint was only found in seven of the 40 specimens and was always a small terminal continuation of the anterior interosseous nerve after the nerve had passed through the pronator quadratus and innervated it. Therefore, we do not recommend division of the anterior interosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…We in turn observed the terminal branch of the AIN running between the PQ’s distal superficial and deep layers in all of our 88 cases. Similar findings have already been described by Svízenská et al (2005), where the AIN terminated by dividing into several fibres inside the PQ in more than 50% of all cases and a continuation to the carpus was only found in seven extremities. The rare detection of the final part of the AIN, beyond its branch to the DRUJ, might be traced back to different embalming procedures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We in turn observed the terminal branch of the AIN running between the PQ’s distal superficial and deep layers in all of our 88 cases. Similar findings have already been described by Svízenská et al (2005), where the AIN terminated by dividing into several fibres inside the PQ in more than 50% of all cases and a continuation to the carpus was only found in seven extremities. The rare detection of the final part of the AIN, beyond its branch to the DRUJ, might be traced back to different embalming procedures.…”
Section: Discussionsupporting
confidence: 90%
“…Our dissected extremities were conserved using Thiel’s solution (Thiel, 1992), which preserves the natural consistence of the tissues and eases preparation of even fine structures, such as articular branches. Concerning the evaluated proximal border of the PQ (Table 2), our results were similar to those of Svízenská et al (2005) who described a range of 4–7 cm, measured from the radiocarpal joint.…”
Section: Discussionsupporting
confidence: 87%
“…According to Safwat and Abdel-Meguid [ 9 ], the PQ muscle is supplied by the motor branches along its whole length. However, Svizenska et al [ 10 ] observed three types of AIN branching patterns: gradual branching, terminal branching, and terminal branches that continue to the wrist joint. Sakamoto et al [ 11 ] also noted that the AIN divided into three or four branches and entered the posterior surface of the PQ muscle and became distributed in various patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [ 16 ] reported that the median distance of the motor branches of AIN from the wrist to the PQ was 4.54 cm. Svizenska et al [ 10 ] reported that the median distance of the origins of muscular branches from the AIN trunk to the wrist joint was 4 cm (range, 2–8 cm). According to Alves et al [ 17 ], the mean point of penetration of AIN branches to the PQ muscle was 3.6 to 3.9 cm above the wrist articular line.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 A terminal sensory branch of the posterior interosseous nerve (PIN) penetrates the extrinsic ligaments of the dorsal capsule and reaches the dorsal subregion of the SLIL (dSLIL). 10,11 The proprioceptive mechanism seems to contribute to the muscle power acting on the wrist and providing dynamic stability beyond the ligamentous static stability. 7 Recent studies have confirmed a reflex arch originating from the dSLIL, following the PIN, and resulting in contraction of the extensor carpi radialis brevis, extensor carpi ulnaris, flexor carpi radialis, and flexor carpi ulnaris.…”
mentioning
confidence: 99%